Study of factors influencing the occurrence of conflicts in pharmacies - Zarichna, T. P.; Chervonenko, N. M.; Brahar, N. O.; Зарічна, Тамара Пантелеймонівна; Червоненко, Наталія Михайлівна; Брагар, Н. О. (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the study was to investigate the factors influencing the occurrence of conflicts in pharmacies during the provision of pharmaceutical care, with the subsequent goal of optimizing the social and psychological climate within the team and improving the quality of service to the population. Materials and methods. Systematic-analytical, mathematical statistical, comparative, and sociological research methods were employed in the study. Descriptive statistics were utilized to present the obtained data. To assess the significance of individual factors, the questionnaire results were converted into corresponding component weights (Wij). Results. The study of conflicts between visitors and pharmacy employees, from the point of view of visitors, revealed several key findings. Most customers expressed dissatisfaction with the prices of medicines and medical devices (Wij = 1.00). Additionally, there were concerns about the perceived quality of the products (Wi j= 0.67), and some customers reported feeling distressed due to the unavailability of necessary medicines (Wij = 0.57). The study, conducted from the point of view of employees, focused on conflicts between employees and visitors. The findings revealed that conflicts most often arise due to dissatisfaction with the prices of medicines and medical devices (Wij = 1.00). Additionally, issues such as requests to dispense over-the-counter medicines from the list of prescription drugs (Wij = 0.70) and returning medicines to the pharmacy after purchase (Wij = 0.67) were identified as contributing factors. The analysis of factors that provoke conflicts in the pharmacy team revealed several key contributors. The most significant include the inadequate behavior of employees (Wij = 1.00), inconsistency in words, assessments, and actions of some team members with the expectations and requirements of others (Wij = 0.89), and psychological incompatibility between employees (Wij = 0.88). The study of conflicts between the administration and subordinates in the pharmacy revealed frequent occurrences linked to several factors. Most notably, conflicts were associated with an imperfect bonus system (Wij = 1.00), high workload (Wij = 0.92), and a perceived lack of career development opportunities (Wij = 0.76). Conclusions. The factors that contribute to the emergence of conflict situations in pharmacies have been identified and studied. Approaches to preventing and resolving conflicts by pharmacy employees are proposed. Мета роботи – дослідження факторів, які впливають на виникнення конфліктів в аптечних закладах при наданні фармацевтичної до- помоги, з подальшою оптимізацією соціально-психологічного клімату в колективі та підвищенням якості обслуговування населення. Матеріали і методи. У роботі використано системно-аналітичний, математико-статистичні, порівняльний і соціологічні методи дослідження. Для репрезентації одержаних даних застосовано методи описової статистики. Для визначення значущості окремих факторів їх оцінки, отримані в результаті анкетування, перераховано до відповідної питомої ваги компоненти (Wij). Результати. Вивчення конфліктів між відвідувачами та співробітниками аптек з погляду відвідувачів показало, що більшість покупців незадоволені цінами на ліки та медичні вироби (Wij = 1,00), мають сумніви щодо їхньої якості (Wij = 0,67), а також покупців пригнічує відсутність потрібних лікарських засобів (Wij = 0,57). Дослідження конфліктів між працівниками та відвідувачами з погляду працівників дало змогу встановити, що найчастіше конфлікти виникають через незадоволеність цінами на ліки і медичні вироби (Wij = 1,00), а також через прохання відпустити ліки без рецепта зі списку рецептурних препаратів (Wij = 0,70) та повернення лікарських засобів в аптеку після придбання (Wij = 0,67). Аналіз факторів, які провокують конфлікти в колективі аптек, засвідчив, що найбільш значущою є неадекватна поведінка співробітників (Wij = 1,00), невідповідність слів, оцінок, вчинків одних членів колективу очікуванням, вимогам інших (Wij = 0,89), а також психологічна несумісність між співробітниками (Wij = 0,88). Вивчення конфліктів між адміністрацією і підлеглими в аптечному закладі засвідчило, що найчастіше конфлікти відбуваються через недосконалу систему преміювання (Wij = 1,00), високий рівень завантаженості (Wij = 0,92) і відсутність можливості кар’єрного зростання (Wij = 0,76). Висновки. Визначено та досліджено фактори, що спричиняють конфліктні ситуації в аптечних закладах. Запропоновано підходи щодо запобігання та розв’язання конфліктів працівниками аптек.
Дослідження факторів, що впливають на виникнення конфліктів в аптечних закладах
Zarichna T. P. - ORCID ID: 0000-0002-3711-4453; Chervonenko N. M. - ORCID ID: 0000-0001-8126-7898;
Keywords: pharmacy; pharmaceutical care; conflict factors; pharmacy visitors; аптека; фармацевтична допомога; конфліктні фактори; відвідувачі аптеки